2015
DOI: 10.1016/j.aller.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A human monoclonal anti-TNF alpha antibody (adalimumab) reduces airway inflammation and ameliorates lung histology in a murine model of acute asthma

Abstract: Adalimumab (a human monoclonal anti-TNF alpha antibody) therapy significantly reduced the severity of lung damage by decreasing cellular infiltration and improvement on the lung histology in a murine model of acute asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
6
12
0
Order By: Relevance
“…Another study demonstrated that the activation of P2X 7 R in rat immune cells promoted the release of IL-6, IL-1β and TNF-α (33). However, the blockade of TNF-α (using adalimumab) and the silencing of TNF-α has been shown to lead to a prolonged inhibitory effect on inflammation in animal models (34)(35)(36). Our data demonstrated that the increasing trend in the expression of IL-1β, IL-6, and TNF-α in the knee joint cartilage tissue of rats with OA was reversed by the P2X 7 R antagonist, AZD9056.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that the activation of P2X 7 R in rat immune cells promoted the release of IL-6, IL-1β and TNF-α (33). However, the blockade of TNF-α (using adalimumab) and the silencing of TNF-α has been shown to lead to a prolonged inhibitory effect on inflammation in animal models (34)(35)(36). Our data demonstrated that the increasing trend in the expression of IL-1β, IL-6, and TNF-α in the knee joint cartilage tissue of rats with OA was reversed by the P2X 7 R antagonist, AZD9056.…”
Section: Discussionmentioning
confidence: 99%
“…Methacholine-induced airway hyperreactivity was also inhibited by infliximab. Similarly, in a murine model of acute asthma, adalimumab therapy reduced lung inflammation and inflammatory cell infiltration (Catal et al, 2014). Local administration of TNFα antisense nucleotide has also been reported to suppress allergic inflammation in mice by reducing release of TNFα and other Th2 cytokines, mucus secretion and inflammatory cell influx (Luo et al, 2012).…”
Section: Role Of Tnfα In Pulmonary Diseasesmentioning
confidence: 99%
“…Moreover, in the past decade, several strategies have been proposed to target TNF receptor as a treatment for asthma (i.e. adalimumab, etanercep, infliximab) 56, 57 and rheumatoid arthritis (i.e. in the DREAM Challenge 8.5 58 , in several cohorts with similar surveys 59–61 and in ref.…”
Section: Discussionmentioning
confidence: 99%